Human reproductive system disturbances and pesticide exposure in Brazil - Sergio Koifman; Rosalina Jorge Koifman; Armando Meyer
The observation of reproductive disturbances in humans and in the wildlife has been reported in the last decade in different countries. Exposure to different chemicals possibly acting in the endocrine system or endocrine disruptors, including pesticides, has been a hypothesis raised to explain the observed changes. This paper aimed to present results of an epidemiological ecologic study carried out to explore population data on pesticides exposure in selected Brazilian states in the eighties and human reproductive outcomes in the nineties. Pearson correlation coefficients were ascertained between available data pesticides sales in eleven states in Brazil in 1985 and selected further reproductive outcomes or their surrogates. Moderate to high correlations were observed to infertility, testis, breast, prostate and ovarian cancer mortality. Despite the restrains of ecologic studies to establish cause-effect relationships, the observed results are in agreement with evidence supporting a possible association between pesticides exposure and the analyzed reproductive outcomes.